Learning Obstacles Siswa SMP dalam Menyelesaikan Operasi Bentuk Aljabar - Valenzeo, Argent Charfo; Sumiaty, Encum (Jurnal Pendidikan Matematika : Judika Education, 2024)
The purpose of this study is to find out the type of learning obstacles experienced by junior high school students in solving algebraic operations. The approach used in this study is a qualitative approach. The instrument used in this study is in the form of items about algebraic operations. The participants in this study were students of class VII and VII of junior high school who had studied algebraic operations. Data was collected through test and interviews through WhatsApp. The results showed that there were several learning obstacles experienced by participants, such as lack of students’ understanding of the concepts used, lack of understanding of students in understanding what is meant, lack of careful reading, students didn’t write down in detail the answers they got, and they’re not familiar with the problems given. Keywords: Learning Obstacles, Algebraic Operations, Study of Mathematics